Commentary on K. M. Bethel, Progress Report on the Project - Davis, Linda Agatha (International Journal of Bahamian Studies, 2016)
Dr Keva M. Bethel, President Emerita of The College of The Bahamas was appointed by The College as Scholar-in-Residence from August 1, 2009 to September 30, 2011. Her brief was to write a book on the history of post-secondary education in The Bahamas, with particular reference to the history of The College of The Bahamas. The report of progress on this assignment, the subject of this commentary, builds upon her preliminary findings, covering the period from August 1, 2009 to April 30, 2010, written before her death in 2011, and published in this volume of the International Journal of Bahamian Studies.